IMPACT OF COVID-19 ON WORKING CAPITAL MANAGEMENT: A THEORETICAL APPROACH - Olowookere, Johnson Kolawole; Odetayo, Tajudeen A.; Adeyemi, Adewumi Zaid; Oyedele, Oloruntoba (Journal of Business And Entrepreneurship, 2022)
This study uses an archival technique to examine the impact of COVID-19 on working capital management. The study reviews previous research published in high-impact journals between 2000 and 2021. In addition, the study uses the risk trade-off theory, market timing theory, and cash conversion cycle theory as lenses to understand the relationship between COVID-19 and working capital management. Both theoretical and empirical reviews indicate that the impact of the COVID19 plague has weakened the finances of business organizations on a global scale. Thus, reviewed theories suggest that for the business organizations to come into the limelight of financial muscle amidst COVID-19, managers should review variable costs and work with their main partners, and access to funds that have been made available to corporate organizations as a result of the mitigation of the COVID-19 plague.